Removal Dynamics of Nitric Oxide (NO) Pollutant Gas by Pulse-Discharged Plasma Technique - Lianshui Zhang; Xiaojun Wang; Weidong Lai; Xueliang Cheng; Kuifang Zhao (The Scientific World Journal)
Nonthermal plasma technique has drawn extensive attentions for removal of air pollutants such as NOx and SO2. The NO removal mechanism in pulse discharged plasma is discussed in this paper. Emission spectra diagnosis indicates that the higher the discharge voltage is, the more the NO are removed and transformed into O, N, N2, NO2, and so forth. Plasma electron temperature Te is ranged from 6400 K at 2.4 kV discharge voltage to 9500 K at 4.8 kV. After establishing a zero-dimensional chemical reaction kinetic model, the major reaction paths are clarified as the electron collision dissociation of NO into N and O during discharge and followed by single substitution of N on NO to form N2 during and after discharge, compared with the small fraction of NO2 formed by oxidizing NO. The reaction directions can be adjusted by N2 additive, and the optimal N2/NO mixing ratio is 2 : 1. Such a ratio not only compensates the disadvantage of electron competitive consumption by the mixed N2, but also heightens the total NO removal extent through accelerating the NO oxidization process.